Preferential growth stimulation of probiotic bacteria by galactan exopolysaccharide from Weissella confusa KR780676. (May 2021) - Devi, Palanisamy Bruntha; Kavitake, Digambar; Jayamanohar, Jabastin; Shetty, Prathapkumar Halady
Graphical abstract: Highlights: Prebiotic potential of galactan exopolysaccharide were studied. Galactan was highly resistant to simulated human digestive enzyme hydrolysis. Galactan effectively stimulated the growth of Lactiplantibacillus plantarum and Limosilactobacillus fermentum. In vitro fecal fermentation showed enhanced short chain fatty acids production. Abstract: Many microbial exopolysaccharides (EPS) are reported to have prebiotic properties. This study reports the prebiotic properties of a galactan exopolysaccharide produced by Weissella confusa KR780676 of fermented food origin. We have reported potential techno-functional properties of this EPS earlier. We have studied the parameters such as enzymatic hydrolysis, growth proliferation effect on probiotic bacteria and in vitro fecal fermentation to demonstrate the prebiotic property of the galactan. The galactan showed strong resistance to simulated human digestive juices such as α-amylase (99.1%), gastric (98.4%) and intestinal fluid hydrolysis (98.8%). It also encouraged the growth of probiotic bacteria viz, Lactobacillus plantarum MTCC9510 (recently reclassified as Lactiplantibacillus plantarum) and L. fermentum MTCC903 (recently reclassified as Limosilactobacillus fermentum) from 6.69 to 9.45 log CFU/mL and 7.13 to 9.05 log CFU/mL respectively in 72 h of fermentation. Carbohydrate utilization also exhibited the same pattern. Fecal fermentation of galactan for 48 h through in vitro studies exhibited significant changes in microbial population and short chain fatty acids (SCFAs) production. Bifidobacterium sp. and Lactobacillus sp. showed significantly ( p  ≤ 0.05) higher growth when compared to Enterococcus sp. (9.62 log CFU/mL, 8.45 log CFU/mL and 8.31 log CFU/mL respectively from 6.54 log CFU/mL) at the end of fermentation. SCFAs (acetic acid, butyric acid and propionic acid production) increased significantly ( p  ≤ 0.05) from 4.53 to 69.12 mM/L, 1.27 to 5.47 mM/L and 0.68 to 42.11 mM/L respectively. These results clearly prove the potential prebiotic property of the galactan EPS and could be used as an effective prebiotic to positively modulate the gut microbiome homeostasis.